Čyževs’kyj und das „barocke Lebensgefühl“ im Prag der 30er Jahre - Vojvodík, Josef (Slovo a smysl : časopis pro mezioborová studia = Word & sense, 2025)
This study approaches Dmitri Čyževs’kyj’s studies on Czech literature in the context of the reception and reflection of the Baroque in Czech culture in the 1930s. This rediscovery and rehabilitation of the Baroque, to which 19th-century historicism and Czech positivist historiography referred to pejoratively as the ‘dark’ period, was not a straightforward process, but was characterized, on the contrary, by a surprising convergence of heterogeneous, even disparate worldviews, as well as ideological, philosophical, and artistic-aesthetic positions. Dmitri Čyževs’kyj’s studies played a significant and interesting role in this process of differentiated reflection and reception of the Czech Baroque. These may be broken down into three concepts: ideological figures that play a pivotal position in Čyževs’kyj’s treatises on Czech and other national literatures of the Baroque and Romantic periods, from a literary aesthetic, hermeneutics, and historical perspective: worldview, antitheticality, and negative allegory.